The Implications and Future Perspectives of Nanomedicine for Cancer Stem Cell Targeted Therapies - Singh, Vimal K.; Saini, Abhishek; Chandra, Ramesh (Frontiers in Molecular Biosciences, 2017)
Cancer stem cells (CSCs) are believed to exhibit distinctive self-renewal, proliferation, and differentiation capabilities, and thus play a significant role in various aspects of cancer. CSCs have significant impacts on the progression of tumors, drug resistance, recurrence and metastasis in different types of malignancies. Due to their primary role, most researchers have focused on developing anti-CSC therapeutic strategies, and tremendous efforts have been put to explore methods for selective eradication of these therapeutically resistant CSCs. In recent years, many reports have shown the use of CSCs- specific approaches such as ATP-binding cassette transporters, blockade of self-renewal and survival of CSCs, CSCs surface markers targeted drugs delivery and eradication of the tumor microenvironment. Also, various therapeutic agents such as small molecule drugs, nucleic acids, and antibodies are said to destroy CSCs selectively. Targeted drug delivery holds the key to the success of most of the anti-CSCs based drugs/ therapies. The convention CSCs- specific therapeutic agents, suffer from various problems. For instance, limited water solubility, small circulation time and inconsistent stability of conventional therapeutic agents have significantly limited their efficacy. Recent advancement in the drug delivery technology has demonstrated that specially designed nanocarrier-based drug delivery approaches (nanomedicine) can be useful in delivering sufficient amount of drug molecules even in the most interiors of CSCs niches and thus can overcome the limitations associated with the conventional free drug delivery methods. The nanomedicine has also been promising in designing effective therapeutic regime against pump-mediated drug resistance (ATP-driven) and reduces detrimental effects on normal stem cells. Here we focus on the biological processes regulating CSCs’ drug resistance and various strategies developed so far to deal with them. We also review the various nanomedicine approaches developed so far to overcome these CSCs related issues and their future perspectives.